2009
DOI: 10.1002/ange.200904028
|View full text |Cite
|
Sign up to set email alerts
|

Selective Amine Cross‐Coupling Using Iridium‐Catalyzed “Borrowing Hydrogen” Methodology

Abstract: Ganz ohne Basen kann der Iridiumkomplex [{Cp*IrI2}2] (Cp*=C5Me5) Kreuzkupplungen von Aminen katalysieren. Eine Reihe von Anilinen wurde in die entsprechenden N‐Isopropyl‐Derivate überführt; die gleiche Reaktion ermöglichte auch die Alkylierung von Benzylaminen und anderen aliphatischen primären Aminen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
20
0
4

Year Published

2010
2010
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(24 citation statements)
references
References 48 publications
0
20
0
4
Order By: Relevance
“…In this respect, the conversion of secondary amines into primary ones is an attractive transformation. Although Williams and co-workers [13] and our group [14] have shown that secondary and even tertiary amines can be activated and used in the alkylation of aliphatic and aromatic amines, to the best of our knowledge no similar reactions with ammonia have been reported, yet.…”
mentioning
confidence: 90%
“…In this respect, the conversion of secondary amines into primary ones is an attractive transformation. Although Williams and co-workers [13] and our group [14] have shown that secondary and even tertiary amines can be activated and used in the alkylation of aliphatic and aromatic amines, to the best of our knowledge no similar reactions with ammonia have been reported, yet.…”
mentioning
confidence: 90%
“…Recently, the CÀC bond formation by borrowing hydrogen (dehydrogenative alcohol activation) has been developed. [11] As far as we are aware, this is the first practical use of hydrogen generated from ethanol in the reductive cyclization of enynes. An enantioselective reductive cyclization in the presence of hydrogen gas and rhodium catalyst had been reported [9b] several years ago and ethanol has been used in diene hydro-hydroxyethylation.…”
mentioning
confidence: 98%
“…Firstly, the reductive alkylation of 4-nitrotoluene with various benzylic alcohols containing methyl, methoxyl, and chloro groups were performed. Clearly, all these reactions progressed well and 83-95 % isolated yields were achieved (entries [1][2][3][4][5]. Then, the alteration of nitrobenzenes was performed.…”
mentioning
confidence: 99%
“…[1] N-Substituted amines are usually prepared by the alkylation of amines with halides. [2] However, this method is problematic due to overalkyation, the toxic nature of halides and related alkylating reagents, and the generation of stoichiometric unwanted byproducts. In many cases, N-substituted amines could also be synthesized by hydroamination [3] and hydroaminomethylation [4] reactions.…”
mentioning
confidence: 99%